Paclitaxel-Eluting Balloon vs Standard Angioplasty to Reduce Restenosis in Diabetic Patients With In-Stent Restenosis of the Superficial Femoral and Proximal Popliteal Arteries: Three-Year Results of the DEBATE-ISR Study. (February 2016) - Grotti, Simone; Liistro, Francesco; Angioli, Paolo; Ducci, Kenneth; Falsini, Giovanni; Porto, Italo; Ricci, Lucia; Ventoruzzo, Giorgio; Turini, Filippo; Bellandi, Guido; Bolognese, Leonardo
Purpose: To report the 3-year safety and effectiveness outcomes from the prospective all-comers DEBATE-ISR study ( ClinicalTrials.gov identifier NCT01558531) of symptomatic diabetic patients with femoropopliteal in-stent restenosis (ISR) undergoing treatment with paclitaxel-eluting balloons compared with historical diabetic controls.Methods: From January 2010 to December 2011, 44 consecutive diabetic patients (mean age 74±11 years; 32 men) were treated with drug-eluting balloons (DEBs) and enrolled in the study. The control group comprised 42 consecutive diabetic patients (age 76±7 years; 23 men) treated with conventional balloon angioplasty (BA) from 2008 to 2009.Results: No significant differences in terms of clinical, angiographic, or procedural characteristics were observed between the study groups. Critical limb ischemia was present in the majority of patients. Tosaka class III ISR was observed in more than half of the patients. Mean lesion length was 132±86 and 137±82 mm in the DEB and BA groups, respectively (p=0.7). At 3-year follow-up, the rate of target lesion revascularization (TLR) was 40% in the DEB group vs 43% in the BA group (p=0.8); Kaplan-Meier analysis showed no significant differences in terms of freedom from TLR. The presence of a Tosaka class III occlusion was associated with a worse outcome in both study groups (odds ratio 3.96, 95% confidence interval 1.55 to 10.1, p=0.004).Conclusion: Using DEBs for femoropopliteal ISR yielded similar results to BA in terms of TLR at 3-year follow-up. The treatment of more complex ISR lesions was associated with an increased rate of TLR, irrespective of the technology used.